Improved race performance in elite middle-distance runners after cumulative altitude exposure - Saunders, P. U.; Telford, R. D.; Pyne, D. B.; Gore, C. J.; Hahn, A. G. (International Journal of Sports Physiology and Performance, 2009)
We quantified the effect of an extended live high-train low (LHTL) simulated altitude exposure followed by a series of training camps at natural moderate altitude on competitive performance in seven elite middle-distance runners (VO2max 71.4 ± 3.4 mL/min·kg, mean ± SD). Runners spent 44 ± 7 nights (mean ± SD) at a simulated altitude of 2846 ± 32 m, and a further 4 ´7- to 10-d training at natural moderate altitude (1700-2200 m) before racing. The combination of simulated LHTL and natural altitude training improved competitive performance by 1.9% (90% confidence limits, 1.3-2.5%). Middle-distance runners can confidently use a combination of simulated and natural altitude to stimulate adaptations responsible for improving performance.